Visual Field Changes Over 5 Years in Patients Treated With Panretinal Photocoagulation or Ranibizumab for Proliferative Diabetic Retinopathy - Maguire, Maureen G. (JAMA Ophthalmol, 2020)
IMPORTANCE: Preservation of peripheral visual field (VF) is considered an advantage for anti–vascular endothelial growth factor agents compared with panretinal photocoagulation (PRP) for treatment of proliferative diabetic retinopathy. Long-term data on VF are important when considering either treatment approach. OBJECTIVE: To further evaluate changes in VF throughout 5 years among eyes enrolled in the Protocol S clinical trial, conducted by the DRCR Retina Network. DESIGN, SETTING, AND PARTICIPANTS: Post hoc analyses of an ancillary study within a multicenter (55 US sites) randomized clinical trial. Individuals with eyes with proliferative diabetic retinopathy enrolled in Protocol S were included. Data were collected from February 2012 to February 2018. Analysis began in June 2018. INTERVENTIONS: Panretinal photocoagulation or intravitreous injections of 0.5-mg ranibizumab. Diabetic macular edema, whenever present, was treated with ranibizumab in both groups. Panretinal photocoagulation could be administered to eyes in the ranibizumab group when failure or futility criteria were met. MAIN OUTCOMES AND MEASURES: Mean change in total point score on VF testing with the Humphrey Field Analyzer 30-2 and 60-4 test patterns. RESULTS: Of 394 eyes enrolled in Protocol S, 234 (59.4%) were targeted for this ancillary study. Of these, 167 (71.4%) had VF meeting acceptable quality criteria at baseline (median [interquartile range] age, 50 [43-58] years; 90 men [53.9%]). At 5 years, 79 (33.8%) had results available. The mean (SD) change in total point score in the PRP and ranibizumab groups was −305 (521) dB and −36 (486) dB at 1 year, respectively, increasing to −527 (635) dB and −330 (645) dB at 5 years, respectively (P = .04). After censoring VF results after PRP treatments in the ranibizumab group, the 5-year mean change in total point score was −201 (442) dB. In a longitudinal regression analysis of change in total point score including both treatment groups, laser treatment was associated with a mean point decrease of 208 (95% CI, 112-304) dB for the initial PRP session, 77 (95% CI, 21-132) dB for additional PRP sessions, and 325 (95% CI, 211-439) dB for endolaser. No association was found between change in point score and the number of ranibizumab injections during the previous year (−9 per injection [95% CI, −22 to 3]). CONCLUSIONS AND RELEVANCE: The limited data available from Protocol S suggest that there are factors besides PRP associated with VF loss in eyes treated for proliferative diabetic retinopathy. Further clinical research is warranted to clarify the finding. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT01489189